Edom at the edge of empire : a social and political history - Crowell, Bradley L. (Atlanta SBL Press, 2021)
"Ancient Edom is best known as the southeastern neighbor of Iron Age Judah that appears in the Hebrew Bible either as Israel's sibling or its reviled enemy. Edom at the Edge of Empire offers an interdisciplinary approach to southern Levantine history that combines biblical, epigraphic, archaeological, and comparative evidence to reconstruct the history of a collection of nomadic tribes and workers in the Wadi Faynan as it relates to the later polity centered around the city of Busayra in the mountains of southern Jordan. This is the first book to incorporate the important evidence from the Wadi Faynan copper mines into a comprehensive account of Edom's history, providing a key resource for students and scholars of the ancient Near East and the Hebrew Bible"--